Websights Beating The Crunch. - Boillot, N.
Internet Protocol version 6 (IPv6) was developed as an alternative to address the very limited features of IPv4. Aside from boosting the number of addresses, IPv6 offers greater security and has several features that improve real-time applications. However, while most Internet routers can accommodate IPv6, only a few organizations are in the process of migrating from the current standard mainly due to financial constraints. As a result, IPv4 and IPv6 may have to coexist for a decade or more
Keywords: IP address; IPsec; IPv4.; IPv6.; Internet protocol version 4.; Internet protocol version 6.; NAT; Network address translation; Networked device; Security standards; Unique number